053 The Provence Diabetes network: management of patients undergoing insulin infusion therapy in South of France. (23rd September 2015) - Ronsin-Pradel, O; Jannot-Lamotte, M F; Atlan, C; Mattei, C; Dicostanzo, V; Plat, F; Delenne, B; Cohen, J; Raccah, D
Abstract : Background and Objectives: Continuous subcutaneous insulin infusion therapy has been in use for more than 20 years. The device was included on the list of reimbursable products and services in France in 2000. At the time, 246 patients were being treated in the Provence-Côte d'Azur region. The Provence Diabetes network was created in order to meet regional organisational needs during device deployment, to establish deployment rules, and to ensure the safety, quality and consistency of practices. Our objective was to assess the results obtained for the year 2008. Programme: The Provence Diabetes network currently includes nine pioneer centres (including two paediatric centres), over 100 endocrinologists in independent practice in charge of treatment follow-up, 13 providers, four device manufacturers, state-registered nurses, dieticians, nonhospital podologists and health care institutions. Results: In 2008, 275 patients started insulin infusion therapy within the network and 1193 patients were undergoing regular monitoring. Overall, 89% of scheduled patients had undergone yearly evaluation. Their average age was 46 years, 84.3% had type 1 diabetes (average duration 19.5 years). They had been on insulin infusion for a mean of 5 years. When insulin infusion therapy was initiated, their glycated haemoglobin (HbA1c) was 8.3%. By the time of the yearly evaluation, their metabolic status had markedly improved; HbAIc had fallen to 7.5% (p<10–9). There were 0.02% episodes of ketoacidosis/patient/year, and 0.1 episodes of severe hypoglycaemia/patient/year. Compliance was good in 85.5% of patients (quarterly follow-up visits, regular dose adjustments, blood glucose levels recorded several times a day). Most patients mastered device use (only 6% needed further training), 85.5% were aware of the insulin substitution protocol in case of pump failure, and 68% knew how to react in an emergency. Discussion and Conclusions: Analysis of metabolic results and patient education in patients evaluated in 2008 within the Provence diabetes network has established the efficiency and safety of continuous subcutaneous insulin infusion therapy at a regional level (better metabolic balance and few acute accidents). This was despite more widespread diffusion of the device after national health insurance coverage was granted. In addition, the network has provided added value as regards application of regulations by ensuring consistency of practices across health care centres and by professionals (common protocols and procedures), organising training, centralising medical device vigilance and making sure that everyone applies the necessary safety criteria. Contexte et objectifs: Le traitement par pompe à infusion sous cutanée existe depuis plus de 20 ans. En 2000, date d'inscription au TIPS, 246 patients sont traités par pompe à insuline dans la région PACA (hors Alpes –Maritimes)- Corse. Pour répondre aux besoins d'organisation régional lors du déploiement de ce traitement, afin d'en fixer les règles et d'en garantir la qualité, la sécurité et l'homogénéité des pratiques le réseau Diabète Provence est créé. Programme: Cette structure regroupe aujourd'hui 9 centres initiateurs (dont 2 pédiatriques), plus de 100 endocrinologues libéraux de suivi, 13 prestataires, 4 fabricants de pompe, des IDE, diététiciens, podologues libéraux et des établissements de santé. Résultats: Au cours de l'année 2008, 275 patients ont débuté un traitement par pompe à insuline au sein du réseau et 1193 sont suivi régulièrement. 89 % des patients à évaluer ont bénéficié d'une évaluation annuelle du traitement par pompe à insuline. L'âge moyen des patients ayant bénéficié d'une évaluation annuelle en 2008 est de 46 ans, 84, 3% des patients présentent un diabète de type 1, la durée moyenne du diabète chez ces patients est de 19, 5 ans, et les patients sont traités par pompe à insuline depuis 5 années en moyenne. L'HbA1c initiale de ces patients lors de la mise sous pompe était de 8.3% et est de 7, 5% lors de l'évaluation annuelle (p< 10 -9), témoignant d'une amélioration notable de l'équilibre métabolique. On a enregistré 0.02 épisodes acidocétosiques par patient par an et 0.1 épisode d'hypoglycémies sévères par patient et par an. La compliance (respect des consultations trimestrielles de suivi, adaptation régulière des doses et contrôles glycémiques pluriquotidiens) est bonne pour 85, 5% des patients, et moyenne dans 13, 9% des cas. La grande majorité des patients maitrise les manipulations techniques (seuls 6% d'entre eux doivent parfaire leurs connaissances), 85, 5% d'entre eux connaissent leur protocole de substitution d'insuline en cas de panne de pompe et 68 % d'entre eux connaissent les conduite à tenir en cas de situation d'urgence. Conclusion: L'analyse des résultats métaboliques et de l'éducation des patients traités par pompe à infusion sous cutanée d'insuline évalués en 2008 au sein du réseau Diabète Provence permet de confirmer, à l'échelle d'une région, l'efficacité et la sécurité du traitement malgré la diffusion du traitement depuis son remboursement (meilleur équilibre métabolique et peu d'accident aigu). Une des plus values du réseau est de veiller à l'application des textes réglementaires en permettant une homogénéisation des pratiques entre les différents centres et professionnels de santé (protocoles et procédures en commun), en organisant la formation des différents intervenants, en centralisant la matériovigilance et en vérifiant que les critères de sécurité soient bien appliqués par tous.